Financial Performance Analysis of KSP KOPDIT Pintu Air Based on CAMEL Method - Gabriel Pito; Titik Mildawati; Fidiana Fidiana (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to describe and analyze the health level of savings and loan cooperatives, namely Capital (capital), Assets (quality of productive assets), Management (management), Earning (profitability), Liquidity (liquidity). The research was conducted at KSP Kopdit Pintu Air Sikka Regency NTT. This type of research is a type of quantitative descriptive research. The data used are financial statements for 2020, 2021 and also the results of interviews from cooperative administrators. While the data analysis technique uses data analysis techniques using the Camel method. This shows that the financial performance of KSP Kopdit Pintu Air using the ratio of the Camel method is in an unhealthy situation, but in 2021 it is slightly healthier or in the moderate category.